Physical activity in non-ambulatory toddlers with cerebral palsy. (July 2019) - Orlando, Julie M.; Pierce, Samuel; Mohan, Mayumi; Skorup, Julie; Paremski, Athylia; Bochnak, Megan; Prosser, Laura A.
Abstract: Background: Children with cerebral palsy are less likely to be physically active than their peers, however there is limited evidence regarding self-initiated physical activity in toddlers who are not able, or who may never be able, to walk. Aims: The aim of this study was to measure self-initiated physical activity and its relationship to gross motor function and participation in non-ambulatory toddlers with cerebral palsy. Methods and procedures: Participants were between the ages of 1–3 years. Physical activity during independent floor-play at home was recorded using a wearable tri-axial accelerometer worn on the child's thigh. The Gross Motor Function Measure-66 and the Child Engagement in Daily Life, a parent-reported questionnaire of participation, were administered. Outcomes and results: Data were analyzed from the twenty participants who recorded at least 90 min of floor-play (mean: 229 min), resulting in 4598 total floor-play minutes. The relationship between physical activity and gross motor function was not statistically significant (r = 0.20; p = 0.39), nor were the relationships between physical activity and participation (r = 0.05−0.09; p = 0.71−0.84). Conclusions and implications: The results suggest physical activity during floor-play is not related to gross motor function or participation in non-ambulatory toddlers with cerebral palsy. Clinicians and researchers should independently measure physical activity, gross motor function, and participation.